2012
DOI: 10.1177/0954411912439824
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage surface failure: An investigation of the rupture rate and morphology in relation to tissue health and hydration

Abstract: This study investigates the rupture rate and morphology of articular cartilage by altering the bathing environments of healthy and degenerate bovine cartilage. Soaking tissues in either distilled water or 1.5 M NaCl saline was performed in order to render the tissues into a swollen or dehydrated state, respectively. Creep compression was applied using an 8 mm flat-ended polished indenter that contained a central pore of 450 µm in diameter, providing a consistent region for rupture to occur across all 105 teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
(84 reference statements)
1
18
1
Order By: Relevance
“…This is of relevance to the earliest stages of osteoarthritis where the cartilage takes in fluid. 9 Our finding is consistent with studies that have found hyper-hydrated cartilage to reduce the loading required for surface rupture 1,27 and that cartilage is stronger following fluid removal. 3 Although, such increased strength is combined with a reduction to the timeframe over which failure occurs 1 possibly by reducing the ability of cartilage to redistribute stress away from the loading site.…”
Section: Susceptibility To Damagesupporting
confidence: 92%
“…This is of relevance to the earliest stages of osteoarthritis where the cartilage takes in fluid. 9 Our finding is consistent with studies that have found hyper-hydrated cartilage to reduce the loading required for surface rupture 1,27 and that cartilage is stronger following fluid removal. 3 Although, such increased strength is combined with a reduction to the timeframe over which failure occurs 1 possibly by reducing the ability of cartilage to redistribute stress away from the loading site.…”
Section: Susceptibility To Damagesupporting
confidence: 92%
“…The ability of a healthy (intact) surface layer to transmit force over a wider loaded region has previously been proposed as a mechanism that AC uses to prevent rupture [34,35] and can also account for how the healthy (intact) surface layer is able to transfer force over a wider loaded area. The downward drawing of the tissues within the central pore region reflects the reaction of the tissue to these forces.…”
Section: Central Pore Indentationmentioning
confidence: 99%
“…A flat-ended polished indenter (8 mm diameter) that contained a 450 μm diameter central pore/hole was selected because it provided a localized region where stresses could generate within the tissue during compression [34,35]. A creep compression rig was utilized for these tests and all tissues remained in distilled water during testing, consistent with a previous employed protocol [13].…”
Section: Indentationmentioning
confidence: 99%
See 2 more Smart Citations